Silicon fertigation with appropriate source reduces water requirement of maize under water deficit - Teixeira, Gelza Carliane Marques [UNESP]; Prado, Renato de Mello [UNESP]; Oliveira, Larissa Trinque de [UNESP]; Souza, João Vitor de Castro [UNESP]; Rocha, Antonio Márcio Souza [UNESP] (Springer Nature, 2022)
Purpose: The objective was to evaluate soluble sources of silicon (Si) applied through fertigation in mitigating water deficit in maize plants. Another objective was to determine the physiological and nutritional effects involved. Methods: The study was carried out in a greenhouse in pots filled with Oxisol. The treatments were arranged in a 3 x 2 factorial scheme, consisting of Si supply from soluble sources: sodium and potassium silicate stabilized with sorbitol (Si-alkali), potassium silicate (Si-K), plus the control (absence of Si); and two soil water regimes: 70% (without deficit) and 30% (severe water deficit) of soil water retention capacity. The experiment used a randomized block design, with six replications. Si was supplied at a concentration of 2 mmol L-1, applied through fertigation. Four applications were performed, starting at 12 days after seedling emergence. Results: The soluble sources of Si applied through fertigation promoted the uptake of this element by maize plants even under water restriction. Si mitigated the damage caused by severe water deficit in maize plants because it kept the relative leaf water content, decreased the cell leakage index, and preserved the content of photosynthetic pigments, which increased quantum efficiency of photosystem II, content and use efficiency of macronutrients, thus leading to greater growth and biomass. Conclusion: The damage caused by severe water deficit in plants can be mitigated by using a relatively low supply of Si through fertigation. Si addition in irrigated crops improves the use of water resources, proving to be a strategy for sustainable agricultural production.
Keywords: Abiotic stress; Beneficial element; Plant nutrition; Water restriction; Zea mays L